Nepal : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nepal. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2020 Article IV Consultation focuses on Nepal's near and medium-term challenges and policy priorities and was prepared before coronavirus disease 2019 became a global pandemic and resulted in unprecedented strains in global trade, commodity and financial markets. During recent years, strong growth in Nepal has been supported by greater political stability, improved electricity supply, and reconstruction activity following the devastating earthquakes in 2015. Additional policies are needed to continue to support inclusive growth, while safeguarding macroeconomic and financial stability. Fiscal policy should remain prudent, and the transition to fiscal federalism carefully managed. Macroprudential measures should remain in place to limit the build-up of financial sector risk. Recent reforms to boost foreign investment need a supportive implementation environment. Strengthening the implementation of monetary policy requires a well-functioning interest rate framework that reduces volatility in short-term interest rates. Less short-term interest rate volatility would support financial market development and improve policy signaling and transmission. The IMF staff emphasizes the need to introduce a standing deposit facility as a first step toward establishing a reliable implementation track record for the interest rate corridor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet